YOGIC PRACTICES FOR HEALTH AND SPORTS PERFORMANCE (International Journal of Food and Nutritional Sciences, 2022)
Significant advancements have been made in a broad number of subfields of science and technology in the 21st century, including space flight, military might, nuclear power, information networks, and computers, to name a few. As a result of the expansion of the internet, it is presently attainable to gain access to info in a brisk and uncomplicated manner from any location in the universe. This paves the way for an entirely new set of opportunities and prospects. Because of the implementation of this scientifically and technologically sophisticated technology, the human capacity for free mobility has been severely restricted. This is a direct consequence of the advancement of technology. It is very obvious that both the degree of stress and the sentiments of competition were amplified to significantly higher levels. It is difficult to refute the reality that mental illness, leading a sedentary lifestyle, and stress all have a detrimental influence on the human body, and this fact simply cannot be ignored. It is also hard to argue against the fact that these three factors have a negative impact on the human body. The significance of yoga needs to finally be understood by the modern man in order for humanity to continue to advance.